2014
DOI: 10.1063/1.4880299
|View full text |Cite
|
Sign up to set email alerts
|

Band-gap nonlinear optical generation: The structure of internal optical field and the structural light focusing

Abstract: A novel approach for the enhancement of nonlinear optical effects inside globular photonic crystals (PCs) is proposed and systematically studied via numerical simulations. The enhanced optical harmonic generation is associated with two- and three-dimensional PC pumping with the wavelength corresponding to different PC band-gaps. The interactions between light and the PC are numerically simulated using the finite-difference time-domain technique for solving the Maxwell's equations. Both empty and infiltrated tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 85 publications
(103 reference statements)
2
17
0
Order By: Relevance
“…Furthermore, the first Stokes component for benzene and the anti-Stokes component for carbon disulfide are located directly in the region of the corresponding stop bands. According to the theory, 18 an anomalous increase in the spectral density of the effective electromagnetic field at the frequency of pump radiation and at the frequencies of SRS should be expected in these cases. This in turn should increase the gain of generation of stimulated Raman scattering and, correspondingly, reduce the threshold of SRS observation.…”
Section: Results Of Experimental Investigationsmentioning
confidence: 99%
“…Furthermore, the first Stokes component for benzene and the anti-Stokes component for carbon disulfide are located directly in the region of the corresponding stop bands. According to the theory, 18 an anomalous increase in the spectral density of the effective electromagnetic field at the frequency of pump radiation and at the frequencies of SRS should be expected in these cases. This in turn should increase the gain of generation of stimulated Raman scattering and, correspondingly, reduce the threshold of SRS observation.…”
Section: Results Of Experimental Investigationsmentioning
confidence: 99%
“…Furthermore, the first Stokes com ponent for benzene and the anti Stokes component for carbon disulfide are located directly in the region of the corresponding stopbands. According to the the ory [24], an anomalous increase in the spectral density of the effective electromagnetic field at the frequency of pump radiation and at the frequencies of stimulated Raman scattering should be expected in these cases. This in turn should increase the gain of generation of stimulated Raman scattering and, correspondingly, reduce the threshold of the observation of stimulated Raman scattering.…”
Section: Reduction Of the Threshold Of Stimulated Raman Scattering Inmentioning
confidence: 97%
“…Similar one dimen sional structures can be used to increase the efficiency of generation of the anti Stokes component of stimu lated Raman scattering, whose intensity under normal conditions is much lower than the intensity of the cor responding Stokes component. It was shown in [24] that the effect of a sharp increase in the spectral energy density of the electromagnetic field near the surface of two and three dimensional photonic crystals occurs when the frequency of the electromagnetic wave is directly in the region of the stopband.…”
Section: Reduction Of the Threshold Of Stimulated Raman Scattering Inmentioning
confidence: 99%
“…It was found that if the pumping wavelength corresponds to the PC BG, k x ¼ k BGi (where i ¼ 1, 2,…, N are indexes of the BG order), the light could penetrate only to a depth of several PC layers. Strong optical field localization in particular near-surface PC regions appears in this case as a result of the structural light focusing phenomenon, 48,49 i.e., as a result of the coherent waveform distortion on the curvature of PC components.…”
mentioning
confidence: 94%
“…48. It was found that if the pumping wavelength corresponds to the PC BG, k x ¼ k BGi (where i ¼ 1, 2,…, N are indexes of the BG order), the light could penetrate only to a depth of several PC layers.…”
mentioning
confidence: 99%